A rechargeable magnesium-air battery and preparation method thereof
By using ether solution of double tetrafluoroethoxy) magnesium borate as an electrolyte and commercial catalyst as an air cathode catalyst in rechargeable magnesium air batteries, combined with modified metal magnesium or magnesium alloy negative electrodes, the problem of poor circulation performance and discharge platform of existing rechargeable magnesium air batteries is solved, and efficient charge and discharge cycles and good electrochemical performance is achieved.
Patent Information
- Application Number
- CN202210849491.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-07-19
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2042-07-19
AI Technical Summary
The circulation performance and discharge platform of existing rechargeable magnesium air batteries are poor, making it difficult to achieve efficient charging and discharge cycles.
A rechargeable magnesium air battery with high discharge platform and good cycle stability was prepared by using a commercial catalyst as the air positive electrode catalyst, combined with a modified metal magnesium or magnesium alloy negative electrode.
It realizes a high discharge platform and good cycle stability of rechargeable magnesium air batteries. The discharge voltage of the first circle can reach 1.2V, and can complete more than 5 stable cycles.
Smart Images

Figure CN115064819B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of development and application of new energy battery materials, and specifically relates to a rechargeable magnesium-air battery and a method for preparing the battery material thereof. Background Art
[0002] Metal-air batteries use oxygen in the air as the positive electrode active material and metal (lithium, zinc, magnesium or aluminum, etc.) as the negative electrode active material. Oxygen reaches the gas-solid-liquid three-phase interface through the gas diffusion electrode and is electrochemically catalytically reduced. At the same time, the metal negative electrode undergoes an oxidation reaction to release electrical energy. In theory, air can provide an unlimited supply of positive electrode reaction materials for metal-air batteries. Among the many types of metal-air battery systems, magnesium-air batteries are a promising candidate. Compared with lithium-air batteries, which are currently the most studied, magnesium metal has the following advantages: (1) There is no dendrite phenomenon in the deposition process of magnesium ions, and its relative activity is weaker than that of lithium, so its safety is better; (2) Magnesium is abundant in the earth's crust (2.33%, while lithium is only 0.0065%), so its price is lower and has cost advantages; (3) Magnesium is a divalent metal and has a higher density than lithium, so its theoretical volume capacity can reach 3833mAh·cm -3 , much higher than lithium (2046mAh·cm -3 ); (4) The theoretical voltage of magnesium-air batteries can reach 2.95V, which is comparable to that of lithium-air batteries (2.91V). Therefore, magnesium-air batteries have the advantages of high theoretical voltage, high capacity, high safety and low cost.
[0003] Magnesium air batteries are divided into primary magnesium air batteries and rechargeable magnesium air batteries. Primary magnesium air batteries are currently studied more, and related products are mainly used in small, lightweight portable power systems, emergency lights and emergency power backup systems, as well as lighthouses and other submarine instruments, monitoring equipment and buoys. Primary magnesium air batteries have also been used in the military field to supply energy for some military detectors. In contrast, there are fewer studies on rechargeable magnesium air batteries. However, the realization of reversibility can not only retain the advantages of high discharge capacity for magnesium air batteries, but also realize the development of large-scale energy storage devices, and has a wide range of application prospects. Therefore, rechargeable magnesium air batteries are a research field with good prospects. At present, the research on rechargeable magnesium air batteries is mainly carried out in organic systems using organic electrolytes. The present invention uses an ether solution of bis(trifluoroethoxy) magnesium borate as a rechargeable magnesium air battery electrolyte, and uses a cheap commercial catalyst as an air positive electrode catalyst. The prepared rechargeable magnesium air battery can be reversibly cycled and charged and discharged, has a high discharge platform, and has better cycle performance than the rechargeable magnesium metal battery reported in existing research, and has great promotion and application value. Summary of the invention
[0004] The inventors of the present application have found that the use of an ether solution of magnesium bis(tetrakis(trifluoroethoxy)borate) as an electrolyte can greatly improve multiple performances of a rechargeable magnesium-air battery, especially after specific modification of the magnesium metal or magnesium alloy used for the negative electrode, the battery performance is better; and the performance is better than a rechargeable magnesium battery composed of a conventional electrolyte and a modified magnesium metal or magnesium alloy.
[0005] Therefore, in one aspect, the present invention provides a rechargeable magnesium-air battery using an ether solution of magnesium bis(tetrakis(trifluoroethoxy)borate as an electrolyte.
[0006] Furthermore, the ether is selected from one or more of tetrahydrofuran, 2-methyltetrahydrofuran, 1,3-dioxolane, ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, dioxane, and polyethylene glycol dimethyl ether; preferably one or more of ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, and polyethylene glycol dimethyl ether.
[0007] Furthermore, the concentration range of the magnesium bis(tetrakis(trifluoroethoxy)borate ether solution is 0.1-1.5 mol / L, and the concentration can be adjusted according to the solubility of the magnesium salt.
[0008] Furthermore, the bis(trifluoroethoxy)borate magnesium ether solution is prepared by the following method:
[0009] Method 1:
[0010] S1, mixing a dibutyl magnesium / hexane solution with trifluoroethanol for reaction under an inert atmosphere, wherein the molar ratio of dibutyl magnesium to trifluoroethanol is 1:0.5-3, to obtain a mixture;
[0011] S2, the solvent of the above mixture in S1 is drained off at room temperature under vacuum, the remaining powder is dissolved in ether, borane-tetrahydrofuran is added and stirred thoroughly, trifluoroethanol is added after mixing to react, and stirring is continued for 10 to 14 hours, wherein the molar ratio of borane, trifluoroethanol and dibutyl magnesium in S1 is 0.5 to 3:4 to 8.5:1;
[0012] S3, draining the solvent from the mixed solution after the reaction in S2 at room temperature under vacuum to obtain bis(trifluoroethoxy)borate magnesium salt;
[0013] S4, dissolving the magnesium bis(tetrakis(trifluoroethoxy)borate obtained in the reaction in S3 in ether, and continuously stirring for 10 to 14 hours to obtain an ether solution of magnesium bis(tetrakis(trifluoroethoxy)borate,
[0014] Method 2:
[0015] S1, under an inert atmosphere, dissolving magnesium borohydride in ether to control the concentration to be 0.05-0.75 mol / L; the ether is selected from one or more of tetrahydrofuran, 2-methyltetrahydrofuran, 1,3-dioxolane, and ethylene glycol dimethyl ether;
[0016] S2, adding trifluoroethanol dropwise to the above solution and stirring continuously to allow magnesium borohydride and trifluoroethanol to fully react, wherein the molar ratio of magnesium borohydride to trifluoroethanol is 1:8 to 1:10, and stirring is continued for 20 to 24 hours;
[0017] S3, draining the solvent from the solution obtained by the reaction in S2 at room temperature and under vacuum, and drying in a vacuum oven at room temperature for 20 to 24 hours to obtain bis(trifluoroethoxy)borate magnesium salt;
[0018] S4, dissolving the magnesium bis(tetrakis(trifluoroethoxy)borate obtained in S3 in ether, and stirring for 6 to 18 hours to obtain an ether solution of magnesium bis(tetrakis(trifluoroethoxy)borate,
[0019] Method three,
[0020] S1, dissolving a magnesium salt in ether to obtain an ether solution of a magnesium salt, wherein the magnesium salt is selected from magnesium chloride, magnesium fluoride, bis(diisopropyl)amide magnesium, magnesium oxide, and magnesium trifluoromethylsulfonate; the ether is selected from one or more of tetrahydrofuran, 2-methyltetrahydrofuran, 1,3-dioxolane, ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, dioxane, and polyethylene glycol dimethyl ether, preferably one or more of diethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, and polyethylene glycol dimethyl ether;
[0021] S2, adding trifluoroethoxyborate dropwise to the ether solution of the above-mentioned magnesium salt, controlling the molar ratio of magnesium to trifluoroethoxyborate in the magnesium salt to be 1:1-6; adding ether solvent for dilution according to the electrolyte concentration requirement, and continuously stirring the reaction for 12-24 hours to obtain an ether solution of magnesium bis(trifluoroethoxy)borate.
[0022] Furthermore, the rechargeable magnesium-air battery uses metal magnesium / magnesium alloy as the negative electrode, wherein the alloying elements in the magnesium alloy are selected from one or more of aluminum, zinc, manganese, silicon, calcium, silver, copper, nickel, gallium, cerium, thorium, zirconium, lead, lithium, tin, strontium, and cadmium; preferably one or more of aluminum, lithium, cerium, lead, indium, tin, and manganese.
[0023] Preferably, the rechargeable magnesium-air battery uses modified metal magnesium / magnesium alloy as the negative electrode, and the modification method comprises:
[0024] S1', under an inert atmosphere, weigh a salt and dissolve it in ether to prepare a solution, and stir for 10 to 14 hours; wherein the salt includes a metal salt and a non-metal salt, the metal element in the metal salt includes one or more of aluminum, zinc, manganese, calcium, silver, copper, nickel, gallium, cerium, thorium, zirconium, lead, lithium, tin, and cadmium, wherein preferably one or more of tin, antimony, germanium, and bismuth; the non-metal element in the non-metal salt includes one or more of fluorine, chlorine, bromine, iodine, and silicon;
[0025] S2', under an inert atmosphere, drop the solution prepared in S1 onto the surface of the metal magnesium / magnesium alloy that has been polished and cut into discs, wash it in ether after the reaction, and then dry it to obtain a modified metal magnesium / magnesium alloy negative electrode.
[0026] Furthermore, the ether in S2' is selected from at least one of tetrahydrofuran, 2-methyltetrahydrofuran, 1,3-dioxolane, ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, dioxane, and polyethylene glycol dimethyl ether.
[0027] Furthermore, the disc in S2' has a thickness of about 100-300 mm.
[0028] Furthermore, in the above-mentioned rechargeable magnesium-air battery, a commercial catalyst is used as an air positive electrode catalyst, which is selected from one or more of manganese dioxide, platinum carbon, ruthenium oxide, iridium oxide, perovskite, carbon nanotubes, carbon black, acetylene black, and graphene, preferably manganese dioxide and carbon black.
[0029] In another aspect, the present invention provides a method for preparing the above-mentioned rechargeable magnesium-air battery, the method comprising:
[0030] S1, adding a proper amount of additive to the ether solution of magnesium bis(trifluoroethoxy)borate, and stirring for 0.5 to 4 hours; wherein the additive is selected from at least one of bromine, iodine, anthracene, and reduced perylene diimide-ethylenediamine; and the additive is added at a concentration of 0 to 0.5 mol / L to obtain an electrolyte;
[0031] S2, grinding the commercial catalyst material, ball-milling the ground catalyst powder with an organic binder and a conductive carbon-based material, and coating the mixture on a commercial hydrophobic conductive substrate as an air positive electrode of a rechargeable magnesium-air battery;
[0032] S3, under an inert atmosphere, the negative electrode, electrolyte, and air positive electrode are assembled into a battery. The battery structure from bottom to top is a perforated positive electrode shell, nickel foam, air positive electrode, diaphragm, negative electrode, nickel foam, and negative electrode shell; the diaphragm adopts a commercial polymer diaphragm, and the nickel foam adopts commercial nickel foam.
[0033] Among them, the addition of additives in S1 is not a necessary step for the rechargeable magnesium-air battery, so the concentration of the additive can be zero. However, when the above additives are added to the electrolyte, the battery performance can be improved, especially in the rechargeable magnesium-air battery using an ether solution of bis(trifluoromethanesulfonyl)imide magnesium (or bis(trifluoromethanesulfonyl)imide magnesium, CAS: 133395-16-1) as the electrolyte, the addition of additives can significantly improve the electrochemical performance of the battery. Because in this conventional electrolyte, the addition of additives can form a protective film on the surface of the metal magnesium negative electrode, inhibiting the passivation effect of the electrolyte on the metal magnesium negative electrode, thereby improving the performance of the magnesium-air battery.
[0034] Furthermore, the organic binder is selected from one or more of polytetrafluoroethylene, polyvinylidene fluoride, carboxymethyl cellulose, styrene-butadiene rubber latex, polyacrylic acid, polyacrylonitrile, hydroxypropyl methyl cellulose and polyvinyl alcohol; preferably polyvinylidene fluoride.
[0035] Furthermore, the conductive carbon-based material is preferably conductive carbon black.
[0036] Furthermore, the inert atmosphere described herein is preferably an argon atmosphere.
[0037] Beneficial Effects
[0038] In the present invention, the use of ether solution of magnesium bis(trifluoroethoxy)borate as an electrolyte can significantly improve the performance of the rechargeable magnesium air battery, including the charge and discharge performance, the first cycle discharge voltage and the cycle stability. In the best embodiment, 5 stable cycles can be achieved, and the first cycle discharge voltage is as high as 1.2V. In addition, the modification of metal magnesium or magnesium alloy can further optimize the battery performance; while the use of conventional electrolyte (such as ether solution of magnesium bis(trifluoromethanesulfonyl)imide) must be combined with metal magnesium / magnesium alloy modified by the method of the present invention as the negative electrode material to obtain a rechargeable and dischargeable air battery, the reason is that the surface of the negative electrode of metal magnesium and magnesium alloy will be passivated by the ether solution of magnesium bis(trifluoromethanesulfonyl)imide, which inhibits the discharge of the battery; therefore, for the rechargeable magnesium air battery using the ether solution of magnesium bis(trifluoromethanesulfonyl)imide as an electrolyte, the metal magnesium negative electrode must be modified.
[0039] By comparing the embodiments and the comparative examples, it can also be seen that the magnesium-air battery using the ether solution of bis(trifluoroethoxy) magnesium borate as the electrolyte only needs to use metallic magnesium for the negative electrode, but its performance is better than the magnesium-air battery using the ether solution of modified metallic magnesium and bis(trifluoromethanesulfonyl)imide magnesium as the electrolyte. Therefore, the bis(trifluoroethoxy) magnesium borate electrolyte has lower requirements for the negative electrode and is more suitable for the magnesium-air battery.
[0040] In addition, for the ether solution of magnesium tetrakis(trifluoroethoxy)borate as the electrolyte, magnesium or magnesium alloy does not need to be modified, and the battery performance is higher. In this electrolyte, compared with metallic magnesium, the battery performance is better when magnesium alloy, modified magnesium or magnesium alloy is used as the negative electrode under the same conditions. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 This is a cyclic charge and discharge voltage curve of the rechargeable magnesium-air battery prepared in Example 1.
[0042] Figure 2 This is a cyclic charge and discharge voltage curve of the rechargeable magnesium-air battery prepared in Example 6.
[0043] Figure 3 This is a cyclic charge and discharge voltage curve of the rechargeable magnesium-air battery prepared in Comparative Example 2.
[0044] Figure 4 This is a cyclic charge and discharge voltage curve of the rechargeable magnesium-air battery prepared in Comparative Example 4.
[0045] Figure 5 This is a cyclic charge and discharge voltage curve of the rechargeable magnesium-air battery prepared in Comparative Example 7. DETAILED DESCRIPTION
[0046] The following non-limiting embodiments may enable a person skilled in the art to more fully understand the present invention, but are not intended to limit the present invention in any way.
[0047] The specific implementation of the present invention is further described below in conjunction with the accompanying drawings and technical solutions.
[0048] Embodiment 1:
[0049] A preparation method for a rechargeable magnesium-air battery comprises the following steps:
[0050] S1, taking an appropriate amount of dibutyl magnesium / hexane solution and trifluoroethanol for mixed reaction under an inert atmosphere, wherein the molar ratio of dibutyl magnesium to trifluoroethanol is 1:2;
[0051] S2, the mixture after the reaction in S1 is dried under vacuum at room temperature, the remaining powder is dissolved in an appropriate amount of ethylene glycol dimethyl ether, and an appropriate amount of borane-tetrahydrofuran is added and stirred thoroughly, after thorough mixing, an appropriate amount of trifluoroethanol is added to react, and stirring is continued for 12 hours, wherein the molar ratio of borane, trifluoroethanol and dibutyl magnesium in S1 is 2:6:1;
[0052] S3, draining the solvent from the mixed solution after the reaction in S2 at room temperature under vacuum to obtain bis(trifluoroethoxy)borate magnesium salt;
[0053] S4, dissolving magnesium tetrakis(trifluoroethoxy)borate in diethylene glycol dimethyl ether to control the concentration to 0.5 mol / L, thereby completing the preparation of the electrolyte;
[0054] S5, use sandpaper to clean the surface of the metal magnesium and cut it into 12 mm diameter discs with a thickness of about 200 mm, and move it into an inert atmosphere for protection as the negative electrode;
[0055] S6, ball-milling a commercially purchased manganese dioxide catalyst, a binder polyvinylidene fluoride, and a conductive carbon black in a mass ratio of 8:1:1, coating the mixture on a commercial hydrophobic conductive substrate after uniform mixing, and drying the substrate; after drying, cutting the substrate into a 12 mm diameter disc-shaped air positive electrode and placing the disc in an inert atmosphere;
[0056] S7, under an inert atmosphere, the negative electrode, electrolyte, and positive electrode are assembled into a rechargeable magnesium-air battery. The battery structure from bottom to top is a perforated positive electrode shell, nickel foam, air positive electrode, diaphragm, negative electrode material, nickel foam, and negative electrode shell; the battery shell uses a commercial 304 stainless steel 2032 type battery shell, the diaphragm uses a commercial polyethylene diaphragm, and the nickel foam uses commercial nickel foam, which is cut into 19 mm diameter discs for use.
[0057] Charge and discharge performance test
[0058] The Wuhan LAND battery performance tester was used to test the charge and discharge curves of the rechargeable magnesium-air battery. The test conditions were set based on the mass of the catalyst active substance, the current density was set to 200 mA / g (catalyst) for constant current charge and discharge, and the capacity was limited to 1000 mAh / g (catalyst).
[0059] according to Figure 1 From the cyclic charge and discharge curve of the rechargeable magnesium-air battery shown, it can be seen that the rechargeable magnesium-air battery can complete more than 5 cycles of charge and discharge, and the first cycle discharge voltage is about 1.2V.
[0060] Embodiment 2:
[0061] A preparation method for a rechargeable magnesium-air battery comprises the following steps:
[0062] S1, taking an appropriate amount of dibutyl magnesium / hexane solution and trifluoroethanol for mixed reaction under an inert atmosphere, wherein the molar ratio of dibutyl magnesium to trifluoroethanol is 1:2;
[0063] S2, the mixture after the reaction in S1 is dried under vacuum at room temperature, the remaining powder is dissolved in an appropriate amount of ethylene glycol dimethyl ether, and an appropriate amount of borane-tetrahydrofuran is added and stirred thoroughly, after thorough mixing, an appropriate amount of trifluoroethanol is added to react, and stirring is continued for 12 hours, wherein the molar ratio of borane, trifluoroethanol and dibutyl magnesium in S1 is 2:6:1;
[0064] S3, draining the solvent from the mixed solution after the reaction in S2 at room temperature under vacuum to obtain bis(trifluoroethoxy)borate magnesium salt.
[0065] S4, dissolving magnesium tetrakis(trifluoroethoxy)borate in diethylene glycol dimethyl ether to control the concentration to 0.5 mol / L, thereby completing the preparation of the electrolyte;
[0066] S5, use sandpaper to clean the surface of the metal magnesium and cut it into 12 mm diameter discs with a thickness of about 200 mm, and move it into an inert atmosphere for protection as the negative electrode;
[0067] S6, ball-milling a commercially purchased platinum-carbon / ruthenium oxide catalyst, a binder polyvinylidene fluoride, and conductive carbon black at a mass ratio of 8:1:1, coating the mixture on a commercial hydrophobic conductive substrate after mixing evenly, and drying the substrate; after drying, cutting the substrate into a 12 mm diameter disc-shaped air positive electrode and placing the disc in an inert atmosphere;
[0068] S7, under an inert atmosphere, the negative electrode, electrolyte, and positive electrode are assembled into a rechargeable magnesium-air battery. The battery structure from bottom to top is a perforated positive electrode shell, nickel foam, air positive electrode, diaphragm, negative electrode material, nickel foam, and negative electrode shell; the battery shell uses a commercial 304 stainless steel 2032 type battery shell, the diaphragm uses a commercial polyethylene diaphragm, and the nickel foam uses commercial nickel foam, which is cut into 19 mm diameter discs for use.
[0069] Charge and discharge performance test
[0070] The Wuhan LAND battery performance tester was used to test the charge and discharge curves of the rechargeable magnesium-air battery. The test conditions were set based on the mass of the catalyst active substance, the current density was set to 200 mA / g (catalyst) for constant current charge and discharge, and the capacity was limited to 1000 mAh / g (catalyst).
[0071] The rechargeable magnesium-air battery completes one cycle of charge and discharge, and the first cycle discharge voltage is about 1.1V.
[0072] Embodiment 3:
[0073] A preparation method for a rechargeable magnesium-air battery comprises the following steps:
[0074] S1, dissolving magnesium borohydride in ethylene glycol dimethyl ether under an inert atmosphere to control the concentration to 0.1 mol / L;
[0075] S2, adding trifluoroethanol dropwise to the above solution and stirring continuously to allow magnesium borohydride and trifluoroethanol to fully react, wherein the molar ratio of magnesium borohydride to trifluoroethanol is 1:8, and stirring is continued for 20 hours;
[0076] S3, draining the solvent from the reaction solution at room temperature under vacuum, and drying in a vacuum oven at room temperature for 20 hours to obtain bis(trifluoroethoxy)borate magnesium salt;
[0077] S4, dissolving the magnesium bis(tetrakis(trifluoroethoxy)borate obtained in S3 in diethylene glycol dimethyl ether, and stirring for 6 hours to obtain magnesium bis(tetrakis(trifluoroethoxy)borate electrolyte;
[0078] S5, use sandpaper to clean the surface of the metal magnesium and cut it into 12 mm diameter discs with a thickness of about 200 mm, and move it into an inert atmosphere for protection as the negative electrode;
[0079] S6, ball-milling a commercially purchased platinum-carbon / ruthenium oxide catalyst, a binder polyvinylidene fluoride, and conductive carbon black at a mass ratio of 8:1:1, coating the mixture on a commercial hydrophobic conductive substrate after mixing evenly, and drying the substrate; after drying, cutting the substrate into a 12 mm diameter disc-shaped air positive electrode and placing the disc in an inert atmosphere;
[0080] S7, under an inert atmosphere, the negative electrode, electrolyte, and positive electrode are assembled into a rechargeable magnesium-air battery. The battery structure from bottom to top is a perforated positive electrode shell, nickel foam, air positive electrode, diaphragm, negative electrode material, nickel foam, and negative electrode shell; the battery shell uses a commercial 304 stainless steel 2032 type battery shell, the diaphragm uses a commercial polyethylene diaphragm, and the nickel foam uses commercial nickel foam, which is cut into 19 mm diameter discs for use.
[0081] Charge and discharge performance test
[0082] The Wuhan LAND battery performance tester was used to test the charge and discharge curves of the rechargeable magnesium-air battery. The test conditions were set based on the mass of the catalyst active substance, the current density was set to 200 mA / g (catalyst) for constant current charge and discharge, and the capacity was limited to 1000 mAh / g (catalyst).
[0083] The rechargeable magnesium-air battery completes one cycle of charge and discharge, and the first cycle discharge voltage is about 1.1V.
[0084] Embodiment 4:
[0085] A preparation method for a rechargeable magnesium-air battery comprises the following steps:
[0086] S1, dissolving magnesium borohydride in ethylene glycol dimethyl ether under an inert atmosphere to control the concentration to 0.1 mol / L;
[0087] S2, adding trifluoroethanol dropwise to the above solution and stirring continuously to allow magnesium borohydride and trifluoroethanol to fully react, wherein the molar ratio of magnesium borohydride to trifluoroethanol is 1:8, and stirring is continued for 20 hours;
[0088] S3, draining the solvent from the reaction solution at room temperature under vacuum, and drying in a vacuum oven at room temperature for 20 hours to obtain bis(trifluoroethoxy)borate magnesium salt;
[0089] S4, dissolving the magnesium bis(tetrakis(trifluoroethoxy)borate obtained in S3 in diethylene glycol dimethyl ether, and stirring for 6 hours to obtain magnesium bis(tetrakis(trifluoroethoxy)borate electrolyte;
[0090] S5, using sandpaper to clean the surface of the magnesium-zinc alloy and then cut it into 12 mm diameter discs with a thickness of about 200 mm, and move it into an inert atmosphere for protection as the negative electrode;
[0091] S6, ball-milling a commercially purchased platinum-carbon / ruthenium oxide catalyst with a binder of polyvinylidene fluoride and conductive carbon black at a mass ratio of 8:1:1, coating the mixture on a commercial hydrophobic conductive substrate after uniform mixing, and drying the substrate; after drying, cutting the substrate into a 12 mm diameter disc-shaped air positive electrode and placing the disc in an inert atmosphere;
[0092] S7, under an inert atmosphere, the negative electrode, electrolyte, and positive electrode are assembled into a rechargeable magnesium-air battery. The battery structure from bottom to top is a perforated positive electrode shell, nickel foam, air positive electrode, diaphragm, negative electrode material, nickel foam, and negative electrode shell; the battery shell uses a commercial 304 stainless steel 2032 type battery shell, the diaphragm uses a commercial polyethylene diaphragm, and the nickel foam uses commercial nickel foam, which is cut into 19 mm diameter discs for use.
[0093] Charge and discharge performance test
[0094] The Wuhan LAND battery performance tester was used to test the charge and discharge curves of the rechargeable magnesium-air battery. The test conditions were set based on the mass of the catalyst active substance, the current density was set to 200 mA / g (catalyst) for constant current charge and discharge, and the capacity was limited to 1000 mAh / g (catalyst).
[0095] The rechargeable magnesium-air battery completes one charge and discharge cycle, and the first cycle discharge voltage is about 1.15V.
[0096] Embodiment 5:
[0097] A preparation method for a rechargeable magnesium-air battery comprises the following steps:
[0098] S1, adding trifluoroethoxy borate dropwise to a solution of magnesium bis(diisopropyl)amide dissolved in tetrahydrofuran, controlling the molar ratio of magnesium to trifluoroethoxy borate in magnesium bis(diisopropyl)amide to be 1:1; continuing to stir the reaction for 20 hours, controlling the magnesium salt concentration to be 0.5 mol / L, to obtain an electrolyte of magnesium bistetrakis(trifluoroethoxy)borate;
[0099] S2, use sandpaper to clean the surface of the magnesium-zinc alloy and cut it into 12 mm diameter discs with a thickness of about 200 mm, and move it into an inert atmosphere for protection;
[0100] S3, under an inert atmosphere, weigh an appropriate amount of stannous chloride and dissolve it in ethylene glycol dimethyl ether to prepare a solution with a concentration of 0.15 mol / L, and stir for 12 h;
[0101] S4, under an inert atmosphere, taking 80 μl of the stirred stannous chloride / ethylene glycol dimethyl ether solution, dropping it on the surface of the magnesium-zinc alloy, reacting for 8 minutes, washing it in ethylene glycol dimethyl ether after the reaction is completed, and drying it to obtain a modified magnesium-zinc alloy negative electrode;
[0102] S5, ball-milling a commercially purchased platinum-carbon / ruthenium oxide catalyst with a binder of polyvinylidene fluoride and conductive carbon black at a mass ratio of 8:1:1, coating the mixture on a commercial hydrophobic conductive substrate after uniform mixing, and drying the substrate; after drying, cutting the substrate into a 12 mm diameter disc-shaped air positive electrode and placing the disc in an inert atmosphere;
[0103] S6, in an inert atmosphere, the negative electrode, electrolyte, and positive electrode are assembled into a rechargeable magnesium-air battery. The battery structure from bottom to top is a perforated positive electrode shell, nickel foam, air positive electrode, diaphragm, negative electrode material, nickel foam, and negative electrode shell; the battery shell uses commercial 304 stainless steel 2032 type battery shell, the diaphragm uses commercial polyethylene diaphragm, and the nickel foam uses commercial nickel foam, which is cut into 19mm diameter discs for use.
[0104] Charge and discharge performance test
[0105] The Wuhan LAND battery performance tester was used to test the charge and discharge curves of the rechargeable magnesium-air battery. The test conditions were set based on the mass of the catalyst active substance, the current density was set to 200 mA / g (catalyst) for constant current charge and discharge, and the capacity was limited to 1000 mAh / g (catalyst).
[0106] The rechargeable magnesium-air battery completes one charge and discharge cycle, and the first cycle discharge voltage is about 1.2V.
[0107] Embodiment 6:
[0108] A preparation method for a rechargeable magnesium-air battery comprises the following steps:
[0109] S1, taking an appropriate amount of dibutyl magnesium / hexane solution and trifluoroethanol for mixed reaction under an inert atmosphere, wherein the molar ratio of dibutyl magnesium to trifluoroethanol is 1:2;
[0110] S2, the mixture after the reaction in S1 is dried under vacuum at room temperature, the remaining powder is dissolved in an appropriate amount of ethylene glycol dimethyl ether, and an appropriate amount of borane-tetrahydrofuran is added and stirred thoroughly, after thorough mixing, an appropriate amount of trifluoroethanol is added to react, and stirring is continued for 12 hours, wherein the molar ratio of borane, trifluoroethanol and dibutyl magnesium in S1 is 2:6:1;
[0111] S3, draining the solvent from the mixed solution after the reaction in S2 at room temperature under vacuum to obtain bis(trifluoroethoxy)borate magnesium salt;
[0112] S4, dissolving magnesium tetrakis(trifluoroethoxy)borate in diethylene glycol dimethyl ether to control the concentration to 0.5 mol / L, thereby completing the preparation of the electrolyte;
[0113] S5, use sandpaper to clean the surface of the metal magnesium and cut it into 12 mm diameter discs with a thickness of about 200 mm, and move it into an inert atmosphere for protection as the negative electrode;
[0114] S6, ball-milling the perovskite catalyst, the binder polyvinylidene fluoride, and the conductive carbon black in a mass ratio of 8:1:1, coating the mixture on a commercial hydrophobic conductive substrate after uniform mixing, and drying the substrate; after drying, cutting the substrate into a 12 mm diameter disc-shaped air positive electrode and moving the disc into an inert atmosphere;
[0115] S7, under an inert atmosphere, the negative electrode, electrolyte, and positive electrode are assembled into a rechargeable magnesium-air battery. The battery structure from bottom to top is a perforated positive electrode shell, nickel foam, air positive electrode, diaphragm, negative electrode material, nickel foam, and negative electrode shell; the battery shell uses a commercial 304 stainless steel 2032 type battery shell, the diaphragm uses a commercial polyethylene diaphragm, and the nickel foam uses commercial nickel foam, which is cut into 19 mm diameter discs for use.
[0116] Charge and discharge performance test
[0117] The Wuhan LAND battery performance tester was used to test the charge and discharge curves of the rechargeable magnesium-air battery. The test conditions were set based on the mass of the catalyst active substance, the current density was set to 200 mA / g (catalyst) for constant current charge and discharge, and the capacity was limited to 1000 mAh / g (catalyst).
[0118] according to Figure 2 From the cyclic charge and discharge curve of the rechargeable magnesium-air battery shown, it can be seen that the rechargeable magnesium-air battery can complete one cycle of charge and discharge, and the battery discharge platform is stable at 1.1V.
[0119] Embodiment 7:
[0120] A preparation method for a rechargeable magnesium-air battery comprises the following steps:
[0121] S1, adding trifluoroethoxy borate dropwise to a solution of magnesium bis(diisopropyl)amide dissolved in tetrahydrofuran, controlling the molar ratio of magnesium to trifluoroethoxy borate in magnesium bis(diisopropyl)amide to be 1:1; continuing to stir the reaction for 20 hours, controlling the magnesium salt concentration to be 0.5 mol / L, to obtain an electrolyte of magnesium bistetrakis(trifluoroethoxy)borate;
[0122] S2, use sandpaper to clean the surface of the metal magnesium and cut it into 12mm diameter discs with a thickness of about 200mm, and move it into an inert atmosphere for protection as the negative electrode;
[0123] S3, ball-milling the perovskite catalyst, the binder polyvinylidene fluoride, and the conductive carbon black in a mass ratio of 8:1:1, coating the mixture on a commercial water-transmitting conductive substrate after uniform mixing, and drying the substrate; after drying, cutting the substrate into a 12 mm diameter disc-shaped air positive electrode and moving the disc into an inert atmosphere;
[0124] S4, in an inert atmosphere, the negative electrode, electrolyte, and positive electrode are assembled into a rechargeable magnesium-air battery. The battery structure from bottom to top is a perforated positive electrode shell, nickel foam, air positive electrode, diaphragm, negative electrode material, nickel foam, and negative electrode shell; the battery shell uses a commercial 304 stainless steel 2032 type battery shell, the diaphragm uses a commercial polyethylene diaphragm, and the nickel foam uses commercial nickel foam, which is cut into 19mm diameter discs for use.
[0125] Charge and discharge performance test
[0126] The Wuhan LAND battery performance tester was used to test the charge and discharge curves of the rechargeable magnesium-air battery. The test conditions were set based on the mass of the catalyst active substance, the current density was set to 200 mA / g (catalyst) for constant current charge and discharge, and the capacity was limited to 1000 mAh / g (catalyst).
[0127] Rechargeable magnesium-air batteries can complete one cycle of charge and discharge, with the first cycle discharge voltage being approximately 1.1V.
[0128] Comparative Example 1:
[0129] S1, taking an appropriate amount of commercially available magnesium bis(trifluoromethanesulfonyl)imide (CAS: 133395-16-1) and dissolving it in diethylene glycol dimethyl ether to control the concentration to 0.5 mol / L, thereby completing the preparation of the electrolyte;
[0130] S2, use sandpaper to clean the surface of the metal magnesium and cut it into 12mm diameter discs with a thickness of about 200mm, and move it into an inert atmosphere for protection as the negative electrode;
[0131] S3, ball-milling a commercially purchased manganese dioxide catalyst, a binder polyvinylidene fluoride, and a conductive carbon black in a mass ratio of 8:1:1, coating the mixture on a commercial hydrophobic conductive substrate after uniform mixing, and drying the substrate; after drying, cutting the substrate into a 12 mm diameter disc-shaped air positive electrode and placing the disc in an inert atmosphere;
[0132] S4, in an inert atmosphere, the negative electrode, electrolyte, and positive electrode are assembled into a rechargeable magnesium-air battery. The battery structure from bottom to top is a perforated positive electrode shell, nickel foam, air positive electrode, diaphragm, negative electrode material, nickel foam, and negative electrode shell; the battery shell uses a commercial 304 stainless steel 2032 type battery shell, the diaphragm uses a commercial polyethylene diaphragm, and the nickel foam uses commercial nickel foam, which is cut into 19mm diameter discs for use.
[0133] Charge and discharge performance test
[0134] The Wuhan LAND battery performance tester was used to test the charge and discharge curves of the rechargeable magnesium-air battery. The test conditions were set based on the mass of the catalyst active substance, the current density was set to 200 mA / g (catalyst) for constant current charge and discharge, and the capacity was limited to 1000 mAh / g (catalyst).
[0135] Rechargeable magnesium-air batteries cannot be charged or discharged.
[0136] Comparative Example 2:
[0137] S1, taking an appropriate amount of commercially available magnesium bis(trifluoromethanesulfonyl)imide (CAS: 133395-16-1) and dissolving it in diethylene glycol dimethyl ether to control the concentration to 0.5 mol / L, thereby completing the preparation of the electrolyte;
[0138] S2, use sandpaper to clean the surface of the metal magnesium and cut it into 12mm diameter discs with a thickness of about 200mm, and move it into an inert atmosphere for protection;
[0139] S3, under an inert atmosphere, weigh an appropriate amount of stannous chloride and dissolve it in ethylene glycol dimethyl ether to prepare a solution with a concentration of 0.15 mol / L, and stir for 12 h;
[0140] S4, under an inert atmosphere, taking 80 μl of the stirred stannous chloride / ethylene glycol dimethyl ether solution, dropping it on the surface of the metal magnesium, reacting for 8 minutes, washing it in ethylene glycol dimethyl ether after the reaction is completed, and drying it to obtain a modified metal magnesium negative electrode;
[0141] S5, ball-milling a commercially purchased manganese dioxide catalyst, a binder polyvinylidene fluoride, and a conductive carbon black in a mass ratio of 8:1:1, coating the mixture on a commercial hydrophobic conductive substrate after uniform mixing, and drying the substrate; after drying, cutting the substrate into a 12 mm diameter disc-shaped air positive electrode and placing the disc in an inert atmosphere;
[0142] S6, in an inert atmosphere, the negative electrode, electrolyte, and positive electrode are assembled into a rechargeable magnesium-air battery. The battery structure from bottom to top is a perforated positive electrode shell, nickel foam, air positive electrode, diaphragm, negative electrode material, nickel foam, and negative electrode shell; the battery shell uses commercial 304 stainless steel 2032 type battery shell, the diaphragm uses commercial polyethylene diaphragm, and the nickel foam uses commercial nickel foam, which is cut into 19mm diameter discs for use.
[0143] Charge and discharge performance test
[0144] The Wuhan LAND battery performance tester was used to test the charge and discharge curves of the rechargeable magnesium-air battery. The test conditions were set based on the mass of the catalyst active substance, the current density was set to 200 mA / g (catalyst) for constant current charge and discharge, and the capacity was limited to 1000 mAh / g (catalyst).
[0145] according to Figure 3 From the cyclic charge and discharge curve of the rechargeable magnesium-air battery shown, it can be seen that the rechargeable magnesium-air battery can complete 4 cycles of charge and discharge, and the discharge voltage of the first cycle is about 0.1V.
[0146] Comparative Example 3:
[0147] S1, taking an appropriate amount of commercially available magnesium bis(trifluoromethanesulfonyl)imide (CAS: 133395-16-1) and dissolving it in diethylene glycol dimethyl ether to control the concentration to 0.5 mol / L, thereby completing the preparation of the electrolyte;
[0148] S2, use sandpaper to clean the surface of the magnesium-zinc alloy and cut it into 12 mm diameter discs with a thickness of about 200 mm, and move it into an inert atmosphere for protection as the negative electrode;
[0149] S3, ball-milling a commercially purchased platinum-carbon / ruthenium oxide catalyst with a binder of polyvinylidene fluoride and conductive carbon black at a mass ratio of 8:1:1, coating the mixture on a commercial hydrophobic conductive substrate after uniform mixing, and drying the substrate; after drying, cutting the substrate into a 12 mm diameter disc-shaped air positive electrode and placing the disc in an inert atmosphere;
[0150] S4, in an inert atmosphere, the negative electrode, electrolyte, and positive electrode are assembled into a rechargeable magnesium-air battery. The battery structure from bottom to top is a perforated positive electrode shell, nickel foam, air positive electrode, diaphragm, negative electrode material, nickel foam, and negative electrode shell; the battery shell uses a commercial 304 stainless steel 2032 type battery shell, the diaphragm uses a commercial polyethylene diaphragm, and the nickel foam uses commercial nickel foam, which is cut into 19mm diameter discs for use.
[0151] Charge and discharge performance test
[0152] The Wuhan LAND battery performance tester was used to test the charge and discharge curves of the rechargeable magnesium-air battery. The test conditions were set based on the mass of the catalyst active substance, the current density was set to 200 mA / g (catalyst) for constant current charge and discharge, and the capacity was limited to 1000 mAh / g (catalyst).
[0153] Rechargeable magnesium-air batteries cannot be charged or discharged.
[0154] Comparative Example 4:
[0155] S1, taking an appropriate amount of commercially available magnesium bis(trifluoromethanesulfonyl)imide (CAS: 133395-16-1) and dissolving it in diethylene glycol dimethyl ether to control the concentration to 0.5 mol / L, thereby completing the preparation of the electrolyte;
[0156] S2, use sandpaper to clean the surface of the metal magnesium and cut it into 12mm diameter discs with a thickness of about 200mm, and move it into an inert atmosphere for protection;
[0157] S3, under an inert atmosphere, weigh an appropriate amount of stannous chloride and dissolve it in ethylene glycol dimethyl ether to prepare a solution with a concentration of 0.15 mol / L, and stir for 12 h;
[0158] S4, under an inert atmosphere, taking 80 μl of the stirred stannous chloride / ethylene glycol dimethyl ether solution, dropping it on the surface of the metal magnesium, reacting for 8 minutes, washing it in pure ethylene glycol dimethyl ether after the reaction is completed, and drying it to obtain a modified metal magnesium negative electrode;
[0159] S5, ball-milling a commercially purchased platinum-carbon / ruthenium oxide catalyst with a binder of polyvinylidene fluoride and conductive carbon black at a mass ratio of 8:1:1, coating the mixture on a commercial hydrophobic conductive substrate after uniform mixing, and drying the substrate; after drying, cutting the substrate into a 12 mm diameter disc-shaped air positive electrode and placing the disc in an inert atmosphere;
[0160] S6, in an inert atmosphere, the negative electrode, electrolyte, and positive electrode are assembled into a rechargeable magnesium-air battery. The battery structure from bottom to top is a perforated positive electrode shell, nickel foam, air positive electrode, diaphragm, negative electrode, nickel foam, and negative electrode shell; the battery shell uses a commercial 304 stainless steel 2032 type battery shell, the diaphragm uses a commercial polyethylene diaphragm, and the nickel foam uses commercial nickel foam, which is cut into 19 mm diameter discs for use.
[0161] Charge and discharge performance test
[0162] The Wuhan LAND battery performance tester was used to test the charge and discharge curves of the rechargeable magnesium-air battery. The test conditions were set based on the mass of the catalyst active substance, the current density was set to 200 mA / g (catalyst) for constant current charge and discharge, and the capacity was limited to 1000 mAh / g (catalyst).
[0163] according to Figure 4 From the cyclic charge and discharge curve of the rechargeable magnesium-air battery shown, it can be seen that the rechargeable magnesium-air battery can complete one cycle of charge and discharge, and the first cycle discharge voltage is about 0.2V.
[0164] Comparative Example 5:
[0165] S1, taking an appropriate amount of commercially available magnesium bis(trifluoromethanesulfonyl)imide (CAS: 133395-16-1) and dissolving it in diethylene glycol dimethyl ether to control the concentration to 0.5 mol / L, thereby completing the preparation of the electrolyte;
[0166] S2, use sandpaper to clean the surface of the magnesium-zinc alloy and cut it into 12 mm diameter discs with a thickness of about 200 mm, and move it into an inert atmosphere for protection;
[0167] S3, under an inert atmosphere, weigh an appropriate amount of stannous chloride and dissolve it in ethylene glycol dimethyl ether to prepare a solution with a concentration of 0.15 mol / L, and stir for 12 h;
[0168] S4, under an inert atmosphere, taking 80 μl of the stirred stannous chloride / ethylene glycol dimethyl ether solution, dropping it on the surface of the magnesium-zinc alloy, reacting for 8 minutes, washing it in pure ethylene glycol dimethyl ether after the reaction is completed, and drying it to obtain a modified magnesium-zinc alloy negative electrode;
[0169] S5, ball-milling a commercially purchased platinum-carbon / ruthenium oxide catalyst with a binder of polyvinylidene fluoride and conductive carbon black at a mass ratio of 8:1:1, coating the mixture on a commercial hydrophobic conductive substrate after uniform mixing, and drying the substrate; after drying, cutting the substrate into a 12 mm diameter disc-shaped air positive electrode and placing the disc in an inert atmosphere;
[0170] S6, in an inert atmosphere, the negative electrode, electrolyte, and positive electrode are assembled into a rechargeable magnesium-air battery. The battery structure from bottom to top is a perforated positive electrode shell, nickel foam, air positive electrode, diaphragm, negative electrode, nickel foam, and negative electrode shell; the battery shell uses a commercial 304 stainless steel 2032 type battery shell, the diaphragm uses a commercial polyethylene diaphragm, and the nickel foam uses commercial nickel foam, which is cut into 19 mm diameter discs for use.
[0171] Charge and discharge performance test
[0172] The Wuhan LAND battery performance tester was used to test the charge and discharge curves of the rechargeable magnesium-air battery. The test conditions were set based on the mass of the catalyst active substance, the current density was set to 200 mA / g (catalyst) for constant current charge and discharge, and the capacity was limited to 1000 mAh / g (catalyst).
[0173] The rechargeable magnesium-air battery can complete one cycle of charge and discharge, and the first cycle discharge voltage is about 0.22V.
[0174] Comparative Example 6:
[0175] S1, taking an appropriate amount of commercially available magnesium bis(trifluoromethanesulfonyl)imide (CAS: 133395-16-1) and dissolving it in diethylene glycol dimethyl ether to control the concentration to 0.5 mol / L, thereby completing the preparation of the electrolyte;
[0176] S2, use sandpaper to clean the surface of the metal magnesium and cut it into 12mm diameter discs with a thickness of about 200mm, and move it into an inert atmosphere for protection as the negative electrode;
[0177] S5, ball-milling the perovskite catalyst, the binder polyvinylidene fluoride, and the conductive carbon black in a mass ratio of 8:1:1, coating the mixture evenly on a commercial water-transmitting conductive substrate, and drying the substrate; after drying, cutting the substrate into a 12 mm diameter disc-shaped air positive electrode and placing the disc in an inert atmosphere;
[0178] S6, in an inert atmosphere, the negative electrode, electrolyte, and positive electrode are assembled into a rechargeable magnesium-air battery. The battery structure from bottom to top is a perforated positive electrode shell, nickel foam, air positive electrode, diaphragm, negative electrode, nickel foam, and negative electrode shell; the battery shell uses a commercial 304 stainless steel 2032 type battery shell, the diaphragm uses a commercial polyethylene diaphragm, and the nickel foam uses commercial nickel foam, which is cut into 19 mm diameter discs for use.
[0179] Charge and discharge performance test
[0180] The Wuhan LAND battery performance tester was used to test the charge and discharge curves of the rechargeable magnesium-air battery. The test conditions were set based on the mass of the catalyst active substance, the current density was set to 200 mA / g (catalyst) for constant current charge and discharge, and the capacity was limited to 1000 mAh / g (catalyst).
[0181] Rechargeable magnesium-air batteries cannot be charged or discharged.
[0182] Comparative Example 7:
[0183] S1, taking an appropriate amount of commercially available magnesium bis(trifluoromethanesulfonyl)imide (CAS: 133395-16-1) and dissolving it in diethylene glycol dimethyl ether to control the concentration to 0.5 mol / L, thereby completing the preparation of the electrolyte;
[0184] S2, use sandpaper to clean the surface of the metal magnesium and cut it into 12mm diameter discs with a thickness of about 200mm, and move it into an inert atmosphere for protection;
[0185] S3, under an inert atmosphere, weigh an appropriate amount of stannous chloride and dissolve it in ethylene glycol dimethyl ether to prepare a solution with a concentration of 0.15 mol / L, and stir for 12 h;
[0186] S4, under an inert atmosphere, taking 80 μl of the stirred stannous chloride / ethylene glycol dimethyl ether solution, dropping it on the surface of the metal magnesium, reacting for 8 minutes, washing it in ethylene glycol dimethyl ether after the reaction is completed, and drying it to obtain a modified metal magnesium negative electrode;
[0187] S5, ball-milling the perovskite catalyst, the binder polyvinylidene fluoride, and the conductive carbon black in a mass ratio of 8:1:1, coating the mixture evenly on a commercial water-transmitting conductive substrate, and drying the substrate; after drying, cutting the substrate into a 12 mm diameter disc-shaped air positive electrode and placing the disc in an inert atmosphere;
[0188] S6, in an inert atmosphere, the negative electrode, electrolyte, and positive electrode are assembled into a rechargeable magnesium-air battery. The battery structure from bottom to top is a perforated positive electrode shell, nickel foam, air positive electrode, diaphragm, negative electrode, nickel foam, and negative electrode shell; the battery shell uses a commercial 304 stainless steel 2032 type battery shell, the diaphragm uses a commercial polyethylene diaphragm, and the nickel foam uses commercial nickel foam, which is cut into 19 mm diameter discs for use.
[0189] Charge and discharge performance test
[0190] The Wuhan LAND battery performance tester was used to test the charge and discharge curves of the rechargeable magnesium-air battery. The test conditions were set based on the mass of the catalyst active substance, the current density was set to 200 mA / g (catalyst) for constant current charge and discharge, and the capacity was limited to 1000 mAh / g (catalyst).
[0191] according to Figure 5 From the cyclic charge and discharge curve of the rechargeable magnesium-air battery shown, it can be seen that the rechargeable magnesium-air battery can complete one cycle of charge and discharge, and the first cycle discharge voltage is about 0.8V.
[0192] Figure 1 , 2 The cyclic charge and discharge curves of the rechargeable magnesium-air battery of Examples 1 and 6 are as follows: Figure 3 , 4 , 5 are respectively the cycle charge and discharge curves of the rechargeable magnesium-air battery of comparative examples 2, 4, and 7. By comparing the charge and discharge performance of the rechargeable magnesium-air battery of Example 1 with comparative examples 1 and 2, Examples 2, 3, 4, and 5 with comparative examples 3, 4, and 5, and Examples 6 and 7 with comparative examples 6 and 7, it can be seen that the rechargeable magnesium-air battery prepared using bis(trifluoroethoxy) magnesium borate electrolyte has better electrochemical performance than the rechargeable magnesium-air battery using the commercially available bis(trifluoromethanesulfonyl)imide magnesium electrolyte under the same conditions; and compared with platinum carbon / ruthenium oxide and perovskite catalysts, the rechargeable magnesium-air battery prepared using the inexpensive commercial MnO2 catalyst as the air positive electrode catalyst and the bis(trifluoroethoxy) magnesium borate electrolyte has the characteristics of a higher discharge platform and better cycle stability.
Claims
1. A rechargeable magnesium-air battery, which uses an ether solution of magnesium bis(trifluoroethoxy)borate as an electrolyte and a metal magnesium / magnesium alloy as a negative electrode, wherein: The alloying elements in the magnesium alloy are selected from one or more of aluminum, zinc, manganese, silicon, calcium, silver, copper, nickel, gallium, cerium, thorium, zirconium, lead, lithium, tin, strontium, and cadmium; a commercial catalyst is used as an air positive electrode catalyst, which is selected from one or more of manganese dioxide, platinum carbon, ruthenium oxide, iridium oxide, perovskite, carbon nanotubes, carbon black, acetylene black, and graphene.
2. A rechargeable magnesium-air battery according to claim 1, characterized in that: The alloying elements in the magnesium alloy are selected from at least one of aluminum, lithium, cerium, lead, indium, tin and manganese.
3. The rechargeable magnesium-air battery according to claim 1, wherein: The ether is selected from one or more of tetrahydrofuran, 2-methyltetrahydrofuran, 1,3-dioxolane, ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, dioxane, and polyethylene glycol dimethyl ether.
4. The rechargeable magnesium-air battery according to claim 1, wherein: The concentration range of the bis(tetrakis(trifluoroethoxy)borate magnesium ether solution is 0.1-1.5 mol / L.
5. The rechargeable magnesium-air battery according to claim 1, wherein: The bis(trifluoroethoxy)borate magnesium ether solution is prepared by the following method: Method 1: S1, mixing a dibutyl magnesium / hexane solution with trifluoroethanol for reaction under an inert atmosphere, wherein the molar ratio of dibutyl magnesium to trifluoroethanol is 1:0.5-3, to obtain a mixture; S2, the solvent of the above mixture in S1 is drained off at room temperature under vacuum, the remaining powder is dissolved in ether, borane-tetrahydrofuran is added and stirred thoroughly, trifluoroethanol is added after mixing to react, and stirring is continued for 10 to 14 hours, wherein the molar ratio of borane, trifluoroethanol and dibutyl magnesium in S1 is 0.5 to 3:4 to 8.5:1; S3, draining the solvent from the mixed solution after the reaction in S2 at room temperature under vacuum to obtain bis(trifluoroethoxy)borate magnesium salt; S4, dissolving the magnesium bis(tetrakis(trifluoroethoxy)borate obtained in the reaction in S3 in ether, and continuously stirring for 10 to 14 hours to obtain an ether solution of magnesium bis(tetrakis(trifluoroethoxy)borate, Method 2: S1, under an inert atmosphere, dissolving magnesium borohydride in ether to control the concentration to be 0.05-0.75 mol / L; the ether is selected from one or more of tetrahydrofuran, 2-methyltetrahydrofuran, 1,3-dioxolane, and ethylene glycol dimethyl ether; S2, adding trifluoroethanol dropwise to the above solution and stirring continuously to allow magnesium borohydride and trifluoroethanol to fully react, wherein the molar ratio of magnesium borohydride to trifluoroethanol is 1:8 to 1:10, and stirring is continued for 20 to 24 hours; S3, draining the solvent from the solution obtained by the reaction in S2 at room temperature and under vacuum, and drying in a vacuum oven at room temperature for 20 to 24 hours to obtain bis(trifluoroethoxy)borate magnesium salt; S4, dissolving the magnesium bis(tetrakis(trifluoroethoxy)borate obtained in S3 in ether, and stirring for 6 to 18 hours to obtain an ether solution of magnesium bis(tetrakis(trifluoroethoxy)borate, Method three, S1, dissolving a magnesium salt in ether to obtain an ether solution of a magnesium salt, wherein the magnesium salt is selected from magnesium chloride, magnesium fluoride, bis(diisopropyl)amide magnesium, magnesium oxide, and magnesium trifluoromethylsulfonate; and the ether is selected from one or more of tetrahydrofuran, 2-methyltetrahydrofuran, 1,3-dioxolane, ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, dioxane, and polyethylene glycol dimethyl ether; S2, adding trifluoroethoxyborate dropwise to the ether solution of the above-mentioned magnesium salt, controlling the molar ratio of magnesium to trifluoroethoxyborate in the magnesium salt to be 1:1-6; adding ether solvent for dilution according to the electrolyte concentration requirement, and continuously stirring the reaction for 12-24 hours to obtain an ether solution of magnesium bis(trifluoroethoxy)borate.
6. The rechargeable magnesium-air battery according to claim 5, wherein: In the third step S1 of the method for preparing the magnesium bis(trifluoroethoxy)borate ether solution, the ether is selected from at least one of diethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether and polyethylene glycol dimethyl ether.
7. The rechargeable magnesium-air battery according to claim 1, wherein: The rechargeable magnesium-air battery uses modified metal magnesium / magnesium alloy as the negative electrode, and the modification method comprises: S1', under an inert atmosphere, weigh a salt, dissolve it in ether to prepare a solution, and stir it for 10 to 14 hours; wherein the salt includes a metal salt and a non-metal salt, the metal element in the metal salt includes one or more of aluminum, zinc, manganese, calcium, silver, copper, nickel, gallium, cerium, thorium, zirconium, lead, lithium, tin, and cadmium; the non-metal element in the non-metal salt includes one or more of fluorine, chlorine, bromine, iodine, and silicon; S2', under an inert atmosphere, drop the solution prepared in S1 onto the surface of the metal magnesium / magnesium alloy that has been polished and cut into discs, wash it in ether after the reaction, and then dry it to obtain a modified metal magnesium / magnesium alloy negative electrode.
8. The rechargeable magnesium-air battery according to claim 7, wherein: The rechargeable magnesium-air battery uses modified metal magnesium / magnesium alloy as the negative electrode, and the metal element in the metal salt in step S1' of the modification method includes one or more of tin, antimony, germanium and bismuth.
9. A method for preparing a rechargeable magnesium-air battery according to any one of claims 1 to 8, comprising: S1, adding a proper amount of additive to the ether solution of magnesium bis(trifluoroethoxy)borate, and stirring for 0.5 to 4 hours; wherein the additive is selected from at least one of bromine, iodine, anthracene, and reduced perylene diimide-ethylenediamine; and the additive is added at a concentration of 0 to 0.5 mol / L to obtain an electrolyte; S2, grinding the commercial catalyst material, ball-milling the ground catalyst powder with an organic binder and a conductive carbon-based material, and coating the mixture on a commercial hydrophobic conductive substrate as an air positive electrode of a rechargeable magnesium-air battery; S3, under an inert atmosphere, the negative electrode, electrolyte, and air positive electrode are assembled into a battery. The battery structure from bottom to top is a perforated positive electrode shell, nickel foam, air positive electrode, diaphragm, negative electrode, nickel foam, and negative electrode shell; the diaphragm adopts a commercial polymer diaphragm, and the nickel foam adopts commercial nickel foam.
10. The preparation method according to claim 9, wherein: The organic binder is selected from one or more of polytetrafluoroethylene, polyvinylidene fluoride, carboxymethyl cellulose, styrene-butadiene rubber latex, polyacrylic acid, polyacrylonitrile, hydroxypropyl methyl cellulose and polyvinyl alcohol.
11. The preparation method according to claim 9, wherein: The conductive carbon-based material is conductive carbon black.